Step-by-step explanation:
(x^4)^3=(x^3)^4 , true
=> x^(4×3) = x^(3×4) = x^12
13^4 x 13^7= (13^4)^7, false
13^(4+7) = 13^11
(13^4)^7 = 13^(4×7) = 13^28
y^5 x y^0/y^3=(y^2)^1 , true
y^5 x y^0/y^3 = y^(5+0-3) = y^2
(y^2)^1 = y^(2×1) = y^2
q^0 x q^5/q^2=(q^3)^2/q^3, true
q^0 x q^5/q^2= q^(0+5-2)= q^3
(q^3)^2/q^3 = q^(3×2-3) = q^3
Answer:
125 ft²
Step-by-step explanation:
We know that that surface area of the triangular prism that will be covered with insulation is equal to the area of the two triangular faces, plus the two lateral rectangular faces.
So you get:
SA = 2 [
(15)(15)] + 2 [(30)(15)] = 1,125 ft²
Answer:
x = 11
Step-by-step explanation:
Sure! but unfortunately the picture is blank. not sure if it’s just my screen